Konstytucyjne ujęcie prawa dostępu do informacji o działalności władz publicznych - Banaszak, Bogusław (Wydawnictwo Naukowe UAM, 2014)
The Constitution of the Republic of Poland contains a set of rights enabling acquisition of diff erent type information (article 51, 54, 61 and 74). This paper focuses on the right of access to public information provided for in Article 61 of the Constitution. The term public information covers each piece of information produced by public bodies and referring to those bodies, as well as each piece of information produced by other entities performing public functions (public offi ce holders) in the scope of their performance of public duties, management of municipal property or the property of the State Treasury, or referring thereto. Organs of public authority likewise public offi ce holders are obliged to provide access to public information. The concept of public authority includes the legislative, executive and judiciary powers as well as territorial self-government (local authorities) commonly considered as an executive power. Article 61 of the Constitution explicitly provides for the right of access to public information pertaining to the activities of public office holders. However, neither in the doctrine nor in judicial decisions, a uniform understanding of a public offi ce holder has been as yet achieved. Taking into account the decisions delivered by the Constitutional Court, however, it must be stated that the concept of a public offi cial is not identical with that of a public offi ce holder. The right of access to information on the activity of organs of public authorities and public offi ce holders (persons performing public functions) is a public subjective right of each citizen, but subject to certain limitations. These include the right to privacy. Yet, the constitutional protection of that right does not extend on the public activity of a person or on the scope of conduct and activities which are generally perceived as being personal or private, but are closely tied to the public activity of such person. Thus, in the event of a confl ict between the right to information and right to privacy, it becomes necessary to establish whether there exists a connection between the information to be made accessible with the performance of a given public function.
Access to public information under Poland’s Constitution
Keywords: the right of access to information on activities of public authorities; the right to privacy; public offi ce holder